PENDAMPINGAN MAJLIS TA’LIM MUSLIMAH NURUL FALAH KELURAHAN SEMPUSARI DALAM TRANSFORMASI PEMBINAAN KEAGAMAAN EKSISTENSI IBU SEBAGAI MADRASATUL ULA PERSPEKTIF ISLAM - Badrun Fawaidi ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2022)
Talking about the transformation of Islamic education is theMuslim taklim assembly, especially in today's digitalizationtechnology in life. The activities of the taklim assembly arenot time bound and can be attended by all levels of society.This article describes the religious activities of the taklimassembly as a transformer of Islamic, social and culturaleducation in society. This article is the result of researchconducted at the Muslimah Nurul Falah Taklim Council,Sempusari through a qualitative approach with the type ofcase study. Data retrieval using in-depth interviews,observations and documents involving five key informantsby purposive sampling. The results of this study are bynature each mandatory so that our lives are always on thepath that is blessed by Allah. The task of education is ashared task starting from the family, the environment/community, the government, but the mostimportant and first is that education is carried out in thefamily and it is the mother who will play more of a role inthe education of her children because the mother is moretogether with the children, and fathers can act as controllersof mother's education. An Islamic education approach isone of the best means to develop all aspects of a child'spersonality, because Islam is a kaffah religion